Boundary layer dynamics during the Ocean‐Atmosphere‐Sea‐Ice‐Snow (OASIS) 2009 experiment at Barrow, AK. Issue 5 (13th March 2014) - Boylan, Patrick; Helmig, Detlev; Staebler, Ralf; Turnipseed, Andrew; Fairall, Chris; Neff, William
Abstract Three‐dimensional atmospheric turbulence measurements were conducted from seven sonic anemometers on two different towers in Barrow, AK, during the spring of 2009 as part of the Ocean‐Atmosphere‐Sea‐Ice‐Snow (OASIS) campaign. This was the largest number of side‐by‐side atmospheric turbulence measurements in the Arctic at one time. These analyses allowed for (1) a comparison of the instrumental measurement approaches and (2) a comparison of the variability of the lower atmospheric surface layer at these measurement heights and tower sites. Friction velocity estimates were affected for a sonic anemometer that was operated on the tower in the near vicinity of a building module. Boundary layer height (BLH) was estimated from sonic anemometer measurements based both on a turbulence variable estimator and a temperature gradient method. Results from both methods were compared to radiosonde‐estimated BLH and generally underestimated the BLH for shallower depths. Conditions with low BLH (< 100 m) often lasted for several days. The seven ozone depletion events (ODE) that were observed during the OASIS campaign had a tendency of coinciding with BLH of less than 50 m and stable atmospheric conditions; however, there was not a clear relationship between the occurrence of ODE and wind speed or wind direction as ODE occurred under a wide range of conditions of BLH, wind speed, local wind direction, and atmospheric stability. Comparisons of these surface layer dynamics to sites in Antarctica and Greenland reveal that boundary layer dynamics are not the primary driving force that fosters the unique ozone chemistry at this coastal Arctic site.